2014
DOI: 10.1590/s0101-73302014000200005
|View full text |Cite
|
Sign up to set email alerts
|

Tendências das desigualdades de acesso ao ensino superior no Brasil: 1982-2010

Abstract: Este trabalho analisa as tendências das desigualdades de acesso ao ensino superior no Brasil ao longo das últimas três décadas, período marcado por grande expansão do sistema de educação superior. São utilizadas informações da Pesquisa Nacional por Amostra de Domicílios (PNAD) e dos Censos Demográficos, a partir das quais modelos de regressão estimam as chances de estudantes que completaram o ensino médio chegarem ao ensino superior no país, em função das origens socioeconômicas, características sociodemográfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
1
1
0
10
Order By: Relevance
“…It is important to stress that the upward socioeconomic mobility discussed here took place not only in terms of income and consumption, but also in relation to schooling, especially among the younger population. As earlier studies have already observed (Salata, 2018b;Picanço, 2015;Mont'Alvão, 2015), along with the changes observed in the income pattern of these families, there was also a notable increase in the presence of their children in universities. with which we identify, it is usual to investigate the impact of objective changes -occupational mobility, income rises, improvements in the standard of the consumption and so on -on the expectations of individuals and their perceptions and attitudes towards inequalities (Lipset & Bendix, 1991;Goldthorpe et al, 1971).…”
Section: Figuresupporting
confidence: 72%
“…It is important to stress that the upward socioeconomic mobility discussed here took place not only in terms of income and consumption, but also in relation to schooling, especially among the younger population. As earlier studies have already observed (Salata, 2018b;Picanço, 2015;Mont'Alvão, 2015), along with the changes observed in the income pattern of these families, there was also a notable increase in the presence of their children in universities. with which we identify, it is usual to investigate the impact of objective changes -occupational mobility, income rises, improvements in the standard of the consumption and so on -on the expectations of individuals and their perceptions and attitudes towards inequalities (Lipset & Bendix, 1991;Goldthorpe et al, 1971).…”
Section: Figuresupporting
confidence: 72%
“…Numerous studies recognise that the social position of families, geographic origin, gender and skin colour condition access and orientation within the Brazilian education system, from primary school to higher education. The possibilities of transition from one school cycle to another are extremely unequal if we look at the quartiles of income of the school population (Montalvão and Arnaldo 2014).…”
Section: A Triple Segregationmentioning
confidence: 99%
“…Several statistic studies show important educational inequalities in the country (ac. HASENBALG; SILVA, 2003;RIBEIRO, 2011;MONT'ALVÃO NETO, 2014). 2-Source: Censo Escolar MEC/Inep and Centro de Informações Educacionais da Secretaria de Estado da Educação, 2015.…”
Section: Este Estudo Procurou Investigar a Chegada De Escolas Privadaunclassified